Molecular and Functional Evolution of the Spermatophyte Sesquiterpene Synthases - Liang, Dongmei (Int J Mol Sci, 2021)
Sesquiterpenes are important defense and signal molecules for plants to adapt to the environment, cope with stress, and communicate with the outside world, and their evolutionary history is closely related to physiological functions. In this study, the information of plant sesquiterpene synthases (STSs) with identified functions were collected and sorted to form a dataset containing about 500 members. The phylogeny of spermatophyte functional STSs was constructed based on the structural comparative analysis to reveal the sequence–structure–function relationships. We propose the evolutionary history of plant sesquiterpene skeletons, from chain structure to small rings, followed by large rings for the first time and put forward a more detailed function-driven hypothesis. Then, the evolutionary origins and history of spermatophyte STSs are also discussed. In addition, three newly identified STSs CaSTS2, CaSTS3, and CaSTS4 were analyzed in this functional evolutionary system, and their germacrene D products were consistent with the functional prediction. This demonstrates an application of the structure-based phylogeny in predicting STS function. This work will help us to understand evolutionary patterns and dynamics of plant sesquiterpenes and STSs and screen or design STSs with specific product profiles as functional elements for synthetic biology application.